Genotype-specific morphophysiological adaptations and proline accumulation uncover drought adaptation complexity in hemp (Cannabis sativa and Cannabis indica) - Mateva, Kumbirai Ivyne; Mahenga, Ein; Matibiri, Terrence; Kamutando, Casper Nyaradzai; Magama, Frank; Dimbi, Susan (Frontiers in Plant Physiology, 2024)
Hemp, which has a wide range of industrial applications, has been marginalized due to its association with marijuana. This stigma has hindered research into improving its resilience to various stressors, resulting in underutilization and neglect. As cultivation expands globally, particularly in hot, dry regions of Africa, understanding drought stress mechanisms in hemp is crucial. This study investigates the drought adaptation mechanisms of three CBD flower hemp genotypes: Cannabis indica (MP) from Switzerland, Cannabis sativa (AQ) from South Africa, and Cannabis sativa (ZB) from Zimbabwe. Conducted under well-watered (WW-75% field capacity [FC]), mild drought (MD-40% FC), and severe drought (SD-0% FC) conditions, the research examines morphophysiological adaptations and proline accumulation in these genotypes, assessed 55 days after transplanting. Results revealed genotype-specific responses to watering regimes. MP demonstrated controlled water use and inherent drought tolerance, maintaining high assimilation rates (A) and superior photosynthetic performance (ΦPSII) under drought conditions. ZB maintained proline levels during drought recovery, suggesting optimized resource allocation and alternative stress-responsive mechanisms, while exhibiting effective morning water use and high non-photochemical quenching (NPQ) for photoprotection. AQ showed conservative water use strategies beneficial in water-limited environments. These findings provide a foundation for breeding programs aimed at developing robust and resilient hemp varieties suited to specific environmental conditions.